Telomere Length and Risk of Incident Fracture and Arthroplasty: Findings From UK Biobank. (13th September 2022) - Curtis, Elizabeth M.; Codd, Veryan; Nelson, Christopher; D'Angelo, Stefania; Wang, Qingning; Allara, Elias; Kaptoge, Stephen; Matthews, Paul M.; Tobias, Jonathan H.; Danesh, John; Cooper, Cyrus; Samani, Nilesh J.; et al.
ABSTRACT: We investigated independent associations between telomere length and risk of fracture and arthroplasty in UK Biobank participants. Leukocyte telomere length (LTL) was measured in baseline samples using a validated polymerase chain reaction (PCR) method. We used, in men and women separately, Cox proportional hazards models to calculate the hazard ratio (HR) for incident fracture (any, osteoporotic) or arthroplasty (hip or knee) over 1, 186, 410 person‐years of follow‐up. Covariates included age, white cell count, ethnicity, smoking, alcohol, physical activity, and menopause (women). In further analyses we adjusted for either estimated bone mineral density (eBMD) from heel quantitative ultrasound, handgrip strength, gait speed, total fat mass (bioimpedance), or blood biomarkers, all measured at baseline (2006–2010). We studied 59, 500 women and 51, 895 men, mean ± standard deviation (SD) age 56.4 ± 8.0 and 57.0 ± 8.3 years, respectively. During follow‐up there were 5619 fractures; 5285 hip and 4261 knee arthroplasties. In confounder‐adjusted models, longer LTL was associated with reduced risk of incident knee arthroplasty in both men (HR/SD 0.93; 95% confidence interval [CI], 0.88–0.97) and women (0.92; 95% CI, 0.88–0.96), and hip arthroplasty in men (0.91; 95% CI, 0.87–0.95), but not women (0.98; 95% CI, 0.94–1.01). Longer LTL was weakly associated with reduced risk of any incident fracture in women (HR/SD 0.96; 95% CI, 0.93–1.00) with less evidence in men (0.98; 95% CI, 0.93–1.02). Associations with incident outcomes were not materially altered by adjustment for heel eBMD, grip strength, gait speed, fat mass, or blood biomarker measures. In this, the largest study to date, longer LTL was associated with lower risk of incident knee or hip arthroplasty, but only weakly associated with lower risk of fracture. The relative risks were low at a population level, but our findings suggest that common factors acting on the myeloid and musculoskeletal systems might influence later life musculoskeletal outcomes. © 2022 The Authors. Journal of Bone and Mineral Research published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research (ASBMR).